Avaliação do limiar nociceptivo e marcadores inflamatórios em ratos após indução de enfisema pulmonar por elastase nos modelos de dor fásica, inflamatória e neuropática - Figueiredo, Rafaella Rocha (2017)
Chronic obstructive pulmonary disease (COPD) is characterized by chronic non-reversible airflow obstruction. Although it compromises the lungs, it also has significant systemic consequences. Individuals with COPD have elevated levels of some inflammatory markers in the blood, such as TNF-α, IL-6 and IL-1-β, such inflammatory markers could be responsible for reducing painful liming in patients with COPD. The present study aims to analyze and determine the relationship of proinflammatory cytokines with the reduction of the nociceptive threshold of rats with COPD, where the disease was induced by porcine pancreatic elastase in a clinical trial. A total of 144 male Wistars rats were submitted to models of phasic pain, inflammatory pain, and neuropathic pain. The results show that animals with COPD, when evaluated by the Tail Flick test, showed early tail withdrawal when compared to the animals in the control group. A significant difference was found for IL-1β, IL-6 and TNF-α in the phasic pain group at the time when the tail removal of animals with COPD was lower, coinciding with higher levels of cytokines. At time 0, after induction of acute CFA hyperalgesia, animals with COPD had a lower pressure threshold than those of naive CFA animals. The levels of IL-1β, IL-6 and TNF-α were higher in plasma in animals with COPD at 24 hours, with significant difference, suggesting that at twenty-four hours after the induction of hyperalgesia by CFA, The cytokines originating from the systemic inflammatory process of COPD associated with the inflammatory mediators of the CFA process led to such an increase, a fact that corroborates with the results found previously. For the neuropathic pain group it is possible to observe results similar to those of the inflammatory pain group. The inflammatory markers in the neuropathic pain group showed a significant difference when we compared the levels of IL-1β, IL-6 and TNF-α in animals without COPD that underwent CCI (saline) surgery, and animals with COPD that also underwent such surgery. Therefore, dpocytic animals present high levels of inflammatory markers, they present altered responses to the noxious stimulus, suggesting that the pathology interferes in the perception of the noxious stimulus. However for the models of inflammatory pain and neuropathic pain, such modifications occur only in the presence of the CFA and CCI stimulus.